Indian Patents & Pharmaceutical Industries - Nakra, Vinod Kumar (International Journal of Pharmaceutical & Biological Archive, 2011)
Patents are instruments which provide exclusive right for a limited period on the patentees for dealing with the product or process of his innovation and prevent others from using them without due authorization. These rights often result in monopolistic pricing of drugs makings them unaffordable to large number of populations particularly from economically developing countries.